EFFICACY AND SAFETY OF INJECTABLE INCRETIN THERAPIES IN THE MANAGEMENT OF OBESITY: A SYSTEMATIC REVIEW - Lopes, Fernanda Rodrigues; Johnson, Travis Ricardo; Ferreira, Fabrício Soares; Lopes, Arthur Alberth; de Amorim, Marcos Antônio; Lima, Theo Gabriel de Matos Nery; Martins, Giovana Abadia Braga; Melo, Nicolas Ferreira; Araujo, Quintiliano Duarte; Dario, Maria Beatriz Almeida; Barbosa, Fernando Daniel Pereira; Sales, Hygor Henrique Silva (Seven Editora, 2026)
Objective: To critically synthesize current scientific evidence regarding the efficacy, safety, and clinical implications of prefilled injectable pens containing glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and dual agonists (GLP-1/GIP) for weight management. Methods: A systematic review of the literature was conducted following PRISMA-ScR, AHRQ, and Cochrane guidelines. Searches were performed in PubMed/MEDLINE, Google Scholar, Embase, Scopus, Web of Science, and ClinicalTrials.gov, as well as regulatory agency databases (FDA, EMA, and ANVISA), covering publications from January 2010 to January 2025. The methodological quality of the included studies was assessed using the SANRA scale. Results: A total of 31 high-quality references were included. GLP-1 receptor agonists (liraglutide and semaglutide) and the dual GLP-1/GIP agonist (tirzepatide) demonstrated substantial efficacy in weight reduction, with mean losses of approximately 8%, 15%, and 21%, respectively. The triple agonist under development, retatrutide, showed promising results, with weight reductions of up to 28%. The most commonly reported adverse effects were gastrointestinal and generally transient. Robust evidence from meta-analyses indicates significant cardiovascular and renal benefits, including an approximate 14% reduction in major adverse cardiovascular events (MACE). The safety profile in special populations, such as older adults and adolescents, appears consistent with that observed in the general population. Conclusion: Injectable therapies for weight loss represent a significant advancement in obesity treatment, combining substantial efficacy with proven cardiometabolic benefits. Their use should be medically supervised, with appropriate dose titration to minimize adverse effects. Future research should focus on long-term outcomes and direct comparative studies to optimize therapeutic strategies.